Comparing some physical properties of Sn93Sb5Zn2, Sn93Sb5Bi2 rapidly solidified alloys (The International Journal for Scientific Research, 2025)
We prepared two of metallic alloys Sn93Sb5Zn2 and Sn93Sb5Bi2 by rapid solidification method. Then, we studied some of their physical properties, including density and unit cell volume. We measured their electrical resistance, from which we determined their electrical resistivity and the temperature coefficient of resistivity. Additionally, we calculated the Fermi parameters. Thermal properties were studied using differential thermal analysis, and mechanical properties were evaluated using the resonance frequency method. We measured the hardness using a Vickers microhardness tester.The results showed that the Sn93Sb5Zn2 alloy has a higher electrical resistivity than Sn93Sb5Bi2 alloy, indicating that Sn93Sb5Bi2 has better electrical conductivity and electronic properties. Regarding thermal properties, the results indicated that the zinc alloy has lower melting temperature, specific heat capacity, and thermal conductivity, but higher thermal diffusivity and enthalpy compared to the bismuth alloy. As for mechanical properties, it was found that the zinc alloy exhibits greater hardness, higher Young's modulus, and lower internal friction, thus possessing better mechanical properties than the bismuth alloy.
Keywords: Alloy; Rapid solidification; Hardness; Fermi Parameters